Uji Daya Ketahanan Beberapa Varietas Cabe Merah (Capsicum annum L.) Terhadap Penyakit Antraknose (Gloeosporium piperatum Ell. et. Ev.) - Rosmayati Rosmayati (Jurnal Agrista, 2008)
Testing of Some Varieties to Antracnose Diseases (Gloeosporium piperatum Ell. et. Ev.)ABSTRACT. One of the limiting factors to develop chilly in Indonesian is antracnose disease. This fungi attacked either young or mature of pod chilly. It was caused by Gloeosporium piperatum. This study were carried out in green house, Faculty of Agriculture, University of North Sumatera. The objective of this research is to find the resistant varieties to antracnose disease and high yield performance. This study arranged in Randomized Block Design (RBD) with 3 replications, respectively. The result showed that varieties King, TM-999, Kingehili, and Taro were more resistant to antracnose disease. While, Northredstar expressed slightly resistant, Taro, Northrestar, King, Kingehili dan TM-999, produced the highest, while Laris produced the lowest yield.